Vazha Keshelava on the Georgia federal structure - Janelidze, Otar (Politics / პოლიტიკა, 2020)
The article discusses several works of V. Keshelava on the territorial organization of the Georgian state. In these publications, V. Keshelava supported the idea of the Georgia federal structure and considered it as a way out of the conflicts.